Brands Equity of Toothpaste Brands in India - Srivastava, R. K.; Singhal, Ankur; Raghavi, Pasupula; Khandelwal, Mudit; Balasubramanian, Srikrishnan; Shirodkar, Swapnil (Indian Journal of Marketing, 2005)
Oral care market in India is quite competitive having many big and small players, HLL commands about 33 per cent of this Rs 2,500-crore market with Pepsodent and Close-up, Colgate is the leader with close to half of the total market. Market research agency ORG puts Anchor White toothpaste share about 7.8 percent, Apart from it Dabur, Ajanta, Aquafresh (GSK), Babool, Promise are other small players fighting for their pie of market share. Recent press reports suggest that Procter and Gamble is set to launch its global oral care brand Crest in India soon. While Colgate-the market leader and with a focus on oral care alone-is certainly likely to face threat of market share erosion by the entry of a new player. Proposed entry of the Giant like P&G has made this segment very volatile and forced the players to evaluate their options once again; Keeping in mind the future Ups and Downs in the Category we have done a analysis to evaluate present Brand equity of the major brands in this Category.